Gamma scintigraphic evaluation of floating gastroretentive tablets of metformin HCl using a combination of three natural polymers in rabbits - Razavi M; Karimian H; Yeong CH; Chung LY; Nyamathulla S; Noordin MI (Dove Medical Press, 2015)
Mahboubeh Razavi,1 Hamed Karimian,1 Chai Hong Yeong,2 Lip Yong Chung,1 Shaik Nyamathulla,1 Mohamed Ibrahim Noordin1,3 1Department of Pharmacy, Faculty of Medicine, University of Malaya, 2Department of Biomedical Imaging and University Malaya Research Imaging Centre, Faculty of Medicine, University of Malaya, 3Center for Natural Products and Drug Discovery (CENAR), Department of Chemistry, Faculty of Science, University of Malaya, Kuala Lumpur, Malaysia Abstract: The present research was aimed at formulating a metformin HCl sustained-release formulation from a combination of polymers, using the wet granulation technique. A total of 16 formulations (F1–F16) were produced using different combinations of the gel-forming polymers: tamarind kernel powder, salep (palmate tubers of Orchis morio), and xanthan. Post-compression studies showed that there were no interactions between the active drug and the polymers. Results of in vitro drug-release studies indicated that the F10 formulation which contained 5 mg of tamarind kernel powder, 33.33 mg of xanthan, and 61.67 mg of salep could sustain a 95% release in 12 hours. The results also showed that F2 had a 55% similarity factor with the commercial formulation (C-ER), and the release kinetics were explained with zero order and Higuchi models. The in vivo study was performed in New Zealand White rabbits by gamma scintigraphy; the F10 formulation was radiolabeled using samarium (III) oxide (153Sm2O3) to trace transit of the tablets in the gastrointestinal tract. The in vivo data supported the retention of F10 formulation in the gastric region for 12 hours. In conclusion, the use of a combination of polymers in this study helped to develop an optimal gastroretentive drug-delivery system with improved bioavailability, swelling, and floating characteristics. Keywords: gastroretentive drug delivery, gamma scintigraphy, sustain-release study, salep, tamarind seed, xanthan